Pendekatan Persaga (Perawat Sahabat Keluarga) untuk Meningkatkan Kemandirian pada Keluarga Binaan di Kelurahan Legok - Mila Triana Sari; Miko Eka Putri; Daryanto Daryanto (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The Healthy Indonesia program begins with a family approach, which is a government program that begins with healthy families, one of which is in the working area of the Putri Ayu Health Center, to be precise, in Legok Village. Families with family members who experience health problems, directly or indirectly will affect the family system. Family friend nurse (Persaga) is a community service program as well as a learning method that makes the family a partner in implementing activities. This program involves students and mentors in dealing with health problems in the community through a family approach so that they can provide experience and understanding related to nursing theory and real applications in solving problems. The purpose of this service is to increase the degree of health in the family by providing assistance to families who meet the criteria for assisted families based on the PERSAGA (Friends of the Family Nurse) approach. This community service will be carried out in the Legok Village, Danau Sipin District in December 2022 - January 2023. The method used is a survey approach, studies, lectures, discussions, demonstrations, simulations, observations and home care. The Community Service Team focuses on community service activities for families who have health problems, counseling according to health problems, making IEC media, demonstrations of herbal therapy, to support the success of the program and suitability with the objectives of the problems in the assisted families. Activities are carried out by integrating courses, and several nursing theories used, namely Friedman, Florence Nightiangle, Dorothea Oream, Marta E Roger, Roy and so on. The outputs obtained are increased knowledge and skills so that families are independent in carrying out family health tasks.